Bio‐Functionalized Manganese Nanoparticles Suppress Fusarium Wilt in Watermelon (Citrullus lanatus L.) by Infection Disruption, Host Defense Response Potentiation, and Soil Microbial Community Modulation. Issue 2 (16th November 2022) - Noman, Muhammad; Ahmed, Temoor; Ijaz, Usman; Shahid, Muhammad; Nazir, Muhammad Mudassir; Azizullah; White, Jason C.; Li, Dayong; Song, Fengming
Abstract: The use of nanofabricated materials is being explored for the potential in crop disease management. Chemically synthesized micronutrient nanoparticles (NPs) have been shown to reduce crop diseases; however, the potential of biogenic manganese NPs (bio‐MnNPs) in disease control is unknown. Here, the potential and mechanism of bio‐MnNPs in suppression of watermelon Fusarium wilt, caused by Fusarium oxysporum f. sp. niveum ( Fon ) are reported. Bio‐MnNPs are synthesized by cell‐free cultural filtrate of a waterrmelon rhizosphere bacterial strain Bacillus megaterium NOM14, and are found spherical in shape with a size range of 27.0–65.7 nm. Application of bio‐MnNPs at 100 µg mL −1 increases Mn content in watermelon roots/shoots and improves growth performance through enhancing multiple physiological processes, including antioxidative capacity. Bio‐MnNPs at 100 µg mL −1 suppress Fusarium wilt through inhibiting colonization and invasive growth of Fon in watermelon roots/stems, and inhibit Fon vegetative growth, conidiation, conidial morphology, and cellular integrity. Bio‐MnNPs potentiate watermelon systemic acquired resistance by triggering the salicylic acid signaling upon Fon infection, and reshape the soil microbial community by improving fungal diversity. These findings demonstrate that bio‐MnNPs suppress watermelon Fusarium wilt by multiple ex planta and in planta mechanisms, and offer a promising nano‐enabled strategy for the sustainable management of crop diseases. Abstract : The current study indicates that Bacillus megaterium NOM14‐synthesized manganese nanoparticles possess the ability to inhibit the phytopathogenic fungus, Fusarium oxysporum f. sp. niveum, and boost the growth and defense responses of watermelon plants, and thus suppress Fusarium wilt in watermelon. These manganese nanoparticles can be utilized both as nano‐pesticides and nano‐fertilizers to achieve a sustainable agriculture system.